open_studier
  • open_studier
.....
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
ya is correct
jim_thompson5910
  • jim_thompson5910
they are basically asking you to solve \(3(x+2) - 4=2\)
jim_thompson5910
  • jim_thompson5910
when you `solve for the inverse function`, you swap x and y, then solve for y so when you plug x = 2 into the inverse, you are really plugging in y = 2 into the original

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

jim_thompson5910
  • jim_thompson5910
did you solve \(3(x+2) - 4 = 2\) for x?
jim_thompson5910
  • jim_thompson5910
Let's check your answer 3(x+2) - 4 = 2 3(8+2) - 4 = 2 ... replace x with 8 3(10) - 4 = 2 30 - 4 = 2 26 = 2 ... this equation is false, so x = 8 is not the solution
jim_thompson5910
  • jim_thompson5910
scroll back up. I explain how you actually replace y with 2
jim_thompson5910
  • jim_thompson5910
f(x) = 3(x+2) - 4 is the same as y = 3(x+2) - 4
jim_thompson5910
  • jim_thompson5910
y = f(x)
anonymous
  • anonymous
I think is y=mx-b
jim_thompson5910
  • jim_thompson5910
yep x = 0 makes 2 = 3(x+2) - 4 true
jim_thompson5910
  • jim_thompson5910
no problem

Looking for something else?

Not the answer you are looking for? Search for more explanations.